2019
DOI: 10.1093/labmed/lmz056
|View full text |Cite
|
Sign up to set email alerts
|

The Study of SALL4 Gene and BMI-1 Gene Expression in Acute Myeloid Leukemia Patients

Abstract: Background In acute myeloid leukemia (AML), many genes have been studied as prognostic markers. SALL4 is expressed constitutively in human leukemia cell lines and primary AML cells. BMI-1 is expressed highly in purified hematopoietic stem cells (HSCs), and its expression declines with differentiation. Objective To study the expression levels of SALL4 and BMI-1 and their clinical significance in patients with AML. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We found that SALL4 gene level was highly expressed among AML group with median value 18.46 (IQR=11.52-83.09) compared to low expression among control group with median value 1.01 (IQR=0.92-1.05) (p <0.001). A previous studies supported our results and showed a significant higher expression of SALL4 among AML patients compared to the control group (p= 0.001) [23] . Moreover, the results of another study concluded that none of the studied controls expressed SALL4 > 1.0 RQ while the cases showed a significant higher expression (p< 0.001) [24] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that SALL4 gene level was highly expressed among AML group with median value 18.46 (IQR=11.52-83.09) compared to low expression among control group with median value 1.01 (IQR=0.92-1.05) (p <0.001). A previous studies supported our results and showed a significant higher expression of SALL4 among AML patients compared to the control group (p= 0.001) [23] . Moreover, the results of another study concluded that none of the studied controls expressed SALL4 > 1.0 RQ while the cases showed a significant higher expression (p< 0.001) [24] .…”
Section: Discussionsupporting
confidence: 92%
“…On studying SALL4 gene expression in AML patients with different FAB subtypes, the highest expression of SALL4 gene level was encountered among patients diagnosed as AML M4 (median = 54.7), followed by AML M2 then M5 then AML M1 (median = 51.47, 22.07 and 21.69, respectively) while the least expression was noticed among patients diagnosed as AML M3 (median = 14.89), yet with no statistical significance (p = 0.7). Partially supporting our results, in their study, Swelem et al [23] found that, in comparison to M1 and M2, SALL4 expression was significantly higher in M4 and M5. Chen et al [26] , on the other hand, discovered that SALL4 gene expression varied considerably with AML FAB subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study has found that indole inhibits the expression of SALL4 mRNA in APL cells and that SALL4 can be regarded as a target in APL [187]. SALL4 is positively related to Bmi-1, which is expressed at markedly higher levels in AML patients [188]. SALL4 mRNA is highly expressed in AML, while it is little expressed in normal hematopoiesis [33].…”
Section: Normal Hematopoietic Function and Leukemiamentioning
confidence: 99%
“…SALL4 promotes self‐renewal and inhibits the differentiation of HSCs in normal hematopoiesis 30 . In human HSCs and leukemic cells, SALL4 increases the expression of Bmi‐1 24,77,78 . Knockdown of SALL4 reduces Bmi‐1 levels in breast cancer cells 79 .…”
Section: Sall4 As a Master Regulator Of Gene Expressionmentioning
confidence: 99%
“…30 In human HSCs and leukemic cells, SALL4 increases the expression of Bmi-1. 24,77,78 Knockdown of SALL4 reduces Bmi-1 levels in breast cancer cells. 79 Furthermore, SALL4 and Bmi-1 expression levels are significantly increased in intrahepatic cholangiocarcinoma cells, indicating a positive correlation between SALL4 and Bmi-1 expression.…”
Section: Sall4 As a Regulator Of Gene Transcriptionmentioning
confidence: 99%